Perceptual Differences Between Patients Who Received Orthodontic Treatment at Orthodontic Specialist, General Dentists, And Dental Technician In Denpasar - Louise Cinthia Hutomo; Mia Ayustina; Teresa Justina (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: The high prevalence of malocclusion in Indonesia, which is as much as 80% of the total population in Indonesia causes the level of Orthodontic treatment to increase. The need for orthodontic treatment in the community is inseparable from the perception of the community in choosing orthodontic treatment and operators. The purpose of this study was to determine differences in perceptions between patients who received orthodontic treatment at orthodontic specialist dentists, general dentists, and dental technician in Denpasar. Method: This study was an observational study with a cross sectional study design with a sample of 108 respondents who received orthodontic treatment at three different operators. Respondents were given a questionnaire with closed questions to determine differences in perceptions between respondents who received orthodontic treatment at all three operators. The data obtained were then analyzed by bivariate and univariate with cross sectional approach with chi square analysis. Results and Discussions: As many as 77.8% of respondents were female and male as many as 22.2%, dominated by respondents aged 21-25 years as many as 33.3% of respondents. Good perception of orthodontic treatment 85.2% and bad as much as 14.8%. With details as many as 36 respondents in orthodontic specialist dentists and general dentists produce good perceptions and 20 respondents in dental technician produce good perceptions, while 16 bad perceptions are found in dental technician. Conclusion: It was concluded that there were differences in perception between patients who received orthodontic treatment at specialist dentists, general dentists, and dentists in Denpasar.